2020
DOI: 10.3389/fcell.2020.00243
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-MIAT-Mediated miR-214-3p Silencing Is Responsible for IL-17 Production and Cardiac Fibrosis in Diabetic Cardiomyopathy

Abstract: As an important complication of diabetes mellitus, diabetic cardiomyopathy (DCM) is characterized by a silent development in its earlier stage and a deficient cardiomyocyte contractility in its late stage. So far, little advance has been achieved to reverse this pathological change. LncRNAs are defined as a large cluster of RNAs without the function of encoding proteins, but have the capacity in controlling gene expression. Interleukin-17 (IL-17), a proinflammatory cytokine, is a key regulator of host inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…51,52 Our previous study also demonstrated that miR-214-3p plays an important role in regulating cardiac pyroptosis by binding to the caspase-1 during diabetic cardiomyopathy progression. 28 Moreover, consistent with the present study, our previous report has documented that the level of miR-214-3p is significantly decreased in patients with DM, 53 which is in agreement with the published data by other groups, 54,55 suggesting the possible implication of our findings in humans. Importantly, the data in the present study showed that the level of miR-214-3p was significantly decreased both in the brains of diabetic mice and in HG-treated neuronal cells, suggesting that miR-214-3p might be involved in the progression of diabetes-induced brain injury.…”
Section: Discussionsupporting
confidence: 93%
“…51,52 Our previous study also demonstrated that miR-214-3p plays an important role in regulating cardiac pyroptosis by binding to the caspase-1 during diabetic cardiomyopathy progression. 28 Moreover, consistent with the present study, our previous report has documented that the level of miR-214-3p is significantly decreased in patients with DM, 53 which is in agreement with the published data by other groups, 54,55 suggesting the possible implication of our findings in humans. Importantly, the data in the present study showed that the level of miR-214-3p was significantly decreased both in the brains of diabetic mice and in HG-treated neuronal cells, suggesting that miR-214-3p might be involved in the progression of diabetes-induced brain injury.…”
Section: Discussionsupporting
confidence: 93%
“…As per the findings of a previous study ( Qi et al, 2020 ), miR-214-3p was shown to target IL-17 ( Figure 5A ). Therefore, we proposed that the observed repression in the expression of IL-17 by anthocyanin might be mediated by miR-214-3p.…”
Section: Resultssupporting
confidence: 89%
“…ChIP assays were performed essentially as described before (Lu et al, 2019). In brief, chromatin in control and that in treated cells were cross-linked with 1% formaldehyde.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%